Temperature dependence of the laminar burning velocity for n-heptane and iso-octane/air flames. (15th September 2020) - Han, Xinlu; Wang, Zhihua; He, Yong; Wang, Shixing; Liu, Yingzu; Konnov, Alexander A.
Highlights: Burning velocity measurements of n-heptane and iso-octane/air flames at 298–358 K. Approaches for cellularity abatement for the heat flux method were discussed and implemented. Burning velocity and its temperature dependence for both fuels were compared with predictions of three models. Extrapolation procedure of the S L measurements was validated using analytical presentation of the method sensitivity. Over-rich phenomena in n-heptane and iso-octane/air flames were observed and analyzed. Abstract: The heat flux method is advantageous for obtaining adiabatic stretch-less flame and measuring laminar burning velocity, S L, with low uncertainty. However, its implementation is sometimes hampered by the instability, manifested as cellularity of the flame stabilized over a flat perforated burner. This paper summarizes the approaches of flame cellularity abatement on the heat flux burner, which are implemented in the present study for measuring burning velocities of n-heptane and iso-octane/air flames. The combination of approaches helped to effectively overcome the cellularity at the fuel-rich side of the tested flames, and the S L was measured at unburnt temperatures T u = 298 K - 358 K and equivalence ratios ϕ = 0.7 - 1.6, at atmospheric pressure, with the S L uncertainty being evaluated. Numerical simulations were carried out using LLNL mechanism, Chaos mechanism and Luong171 mechanism, and the results agree well with the experimental data. From the obtained experimental and numerical S L data, the temperature coefficients α in S L S L 0 = T u T u 0 α as well as the overall activation energy, E a, were derived. It was noted that for n-heptane and iso-octane/air flames, the tendencies of the α and E a against ϕ resemble those for methane, ethane, and propane/air flames. Distinct over-rich flame structures were observed and discussed for n-heptane and iso-octane/air flames around ϕ ≥ 1.5. Moreover, extrapolation proced/ure of the S L measurements was validated using analytical presentation of the heat flux method sensitivity, s vs. c p α ∗ - 1, and other parameters involved in the data processing, which may help to improve the accuracy of future experiments.